The Driver Perception Analysis of Roundabout Intersection: A Case of Basecamp Intersection Batam - Ryan Maro; Andri Irfan Rifai; Joewono Prasetijo (International Journal Labs, 2022)
Signalized intersections and roundabouts are two types of intersections with different systems. The roundabout at Basecamp intersection, in exchange for signalized intersection in the past, is a new thing in that area. This study aims to determine the opinions of basecamp intersection users who used signalized intersections before switching to the roundabout. The effectiveness of using roundabouts compared to the signalized intersection is measured from users' experience of the basecamp intersection as a benchmark. The user-experience-based questionnaire is the primary method to obtain the user's data which is presented in the form of an average scale of performance for each parameter on the radar graph. In total, roundabout outperforms signalized intersection slightly. However, there are significant gaps in performance on driver distraction-free and traffic flow where roundabouts lead. On the other side, signalized intersections significantly dominated the performance of pedestrians' safety. Meanwhile, there are slight differences in drivers' safety and a respectable gap in drivers' ability where signalized intersections lead.